Heteroatom Promoted Ni/Al2O3 Catalysts for Highly Efficient Hydrogenation of 1, 4‐Butynediol to 1, 4‐Butenediol. Issue 32 (27th August 2020) - Wu, Hongli; Ma, Fengyun; Wang, Yuelan; Zeng, Yan; Wu, Hao; Yin, Shuangjie; Mian, Inamullah; Tsubaki, Noritatsu
Abstract: A series of nickel‐based catalysts were prepared by solution combustion synthesis (SCS), using Ce, Ag, Mo, Fe, or Co as a promoter, and applied for efficient and selective hydrogenation of 1, 4‐butynediol (BYD) to 1, 4‐butenediol (BED). It was found that each catalyst containing promoter had higher conversion of BYD and higher selectivity of BED than that of pristine Ni/Al2 O3 catalyst. Among as‐prepared catalysts, Ni−Fe/Al2 O3 exhibited the highest activity and stability toward selective hydrogenation of BYD to BED. Results revealed that the improved catalytic performance of Ni−Fe/Al2 O3 over those of Ni/Al2 O3 could be ascribed to the varied metal‐support interaction and active site dispersion, as well as the formation of Ni−Fe taenite. DFT calculations further demonstrated that the introduction of Fe regulated the adsorption strength of BYD and H on the surface of the catalyst, thus improving the catalytic hydrogenation activity of BYD. Abstract : A series of Ni/Al2 O3 and Ni−M/Al2 O3 (M=Ce, Ag, Mo, Fe, and Co) catalysts were synthesized through solution combustion synthesis (SCS) method. The nickel‐based catalyst by modification with promoters displayed higher 1, 4‐butynediol (BYD) catalytic activity toward hydrogenation and enhanced 1, 4‐butenediol (BED) selectivity than bare Ni/Al2 O3 . The utilization of Fe promoted the reducibility of active nickel sites, forming a benign intimate contact among Ni and Fe oxide species, oxygen vacancies, and stabilizing the catalyst activity.